The Role of Taman Pendidikan Al-Qur’an in Instilling the Students’ Principles of the Importance of Seek Islamic Education at Pondok Pesantren - Alfi Hulwatun Nasichah (Proceeding International Conference on Religion, Science and Education, 2023)
One of the key elements influencing human civilization is education. Currently, the world has advanced. Every aspect of life has been impacted by globalization. There are several effects of the globalization trend and the rapid advancement of technology. Besides have positive effects, technology can also give negative effects, such as making kids unmotivated to study especially about Islamic Education and recite the Holy Al- Qur’an because they spend too much time on their Handphone and television. It will undoubtedly cause the children’s moral decadence. However, Sidengen Village in the Madukara District, specifically at Taman Pendidikan Al-Qur’an (TPQ) Al-Falah Sidengen, has some fascinating things to be investigating. Because most of the pupils at TPQ Al-Falah decided to continue their education after finishing elementary school at the Junior High School, which was affiliated with Pondok Pesantrenl. The goal of this study is to identify the role of Taman Pendidikan Al-Qur’an (TPQ) and the real driving forces behind the high levels of students’ motivation to continue their formal education which is integrated with Pondok Pesantren. This study is using a qualitative approach. Based on the data that the researcher found, it can be concluded that there are some factors that influence students’ principles and there are big roles of TPQ in instilling the students’ principles of the importance of Seek Islamic Education at Pondok Pesantren such as the teachers’ influence and the various method that TPQ used.